An Overview of Tools to Score Severity in Pediatric Inflammatory Bowel Disease - Shaoul, Ron; Day, Andrew S. (Frontiers in Pediatrics, 2021)
Background and Aims: The management of IBD entails the use of various treatments (nutrition, medications, and surgery) in order to induce and maintain remission. The assessment of IBD disease activity is based on a combination of symptoms, clinical findings, imaging, and endoscopic procedures. As in any disease, reliable assessment of disease activity or severity is required in order to plan relevant follow-up, decide on appropriate investigations, determine the best treatment option and subsequently assess response to treatment. It is important for proper documentation, follow-up, assessment of response to treatment and communication, especially in patients with IBD, to talk the same language by using validated and widely used scores for disease activity, endoscopic and radiologic activity, and patient reported outcomes both for clinical practice and research. This review aims to highlight key tools available for the assessment of disease activity or severity in individuals (especially children) with IBD. Methods: A literature search was performed using MEDLINE, Pubmed, and the Cochrane Library with the last search date of August 2020. Tools evaluating disease severity across various aspects (clinical, endoscopic, and radiological) were identified and discussed. Those tools validated and specific for children with IBD were included were available. Results: Over time a number of scoring systems have been developed to quantify clinical, endoscopic and imaging assessments in individuals with IBD. While some are exclusively for children or adults, others appear to have relevance to all age groups. In addition, some tools developed in adult populations are utilized in children, but have not expressly been validated in this age group. Conclusions: Although some available scoring tools are appropriate for children with IBD, others require consideration. The development and use of pediatric-specific tools is relevant and appropriate to optimal care of children and adolescents with IBD.